Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/diagnostics12112772
|View full text |Cite
|
Sign up to set email alerts
|

The Entity of Connshing Syndrome: Primary Aldosteronism with Autonomous Cortisol Secretion

Abstract: Connshing syndrome (CoSh) (adrenal-related synchronous aldosterone (A) and cortisol (C) excess) represents a distinct entity among PA (primary hyperaldosteronisms) named by W. Arlt et al. in 2017, but the condition has been studied for more than 4 decades. Within the last few years, this is one of the most dynamic topics in hormonally active adrenal lesions due to massive advances in steroids metabolomics, molecular genetics from CYP11B1/B2 immunostaining to genes constellations, as well as newly designated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 193 publications
0
7
0
Order By: Relevance
“…HBS is a rare postoperative complication in some patients with PHPT, and the mechanism is the action of osteoclasts after radical resection of PC. 5,14 After radical resection of PC, the sudden decrease of PTH, which acts on bone resorption of osteoclasts does not affect the process of osteogenesis of osteoblasts; osteoclasts activity is replaced by osteoblasts activity, resulting in a rapid increase of calcium uptake, which leads to a large amount of serum calcium into the bone and deposit in the bone tissues, inducing severe symptomatic hypocalcemia such as numbness of perioral sites and fingertips, tetany, and even dyspnea. Studies have been reported currently that risk factors of occurrence of HBS include high PTH with a previous long-term elevated concentration, high calcium levels, and excessive ATP elevation, and so forth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HBS is a rare postoperative complication in some patients with PHPT, and the mechanism is the action of osteoclasts after radical resection of PC. 5,14 After radical resection of PC, the sudden decrease of PTH, which acts on bone resorption of osteoclasts does not affect the process of osteogenesis of osteoblasts; osteoclasts activity is replaced by osteoblasts activity, resulting in a rapid increase of calcium uptake, which leads to a large amount of serum calcium into the bone and deposit in the bone tissues, inducing severe symptomatic hypocalcemia such as numbness of perioral sites and fingertips, tetany, and even dyspnea. Studies have been reported currently that risk factors of occurrence of HBS include high PTH with a previous long-term elevated concentration, high calcium levels, and excessive ATP elevation, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been reported currently that risk factors of occurrence of HBS include high PTH with a previous long-term elevated concentration, high calcium levels, and excessive ATP elevation, and so forth. 5,15,16 Active preoperative measures may reduce the incidence of postoperative HBS, Davenport and Stearns reported that preoperative pamidronate in combination with high doses of oral alfacalcidol and calcium supplements can prevent postoperative symptomatic hypocalcemia and help to prevent the occurrence of HBS. 17 In our case, the patient was given intravenous zoledronic acid combined with oral calcitriol before the operation in order to prevent the occurrence of HBS after parathyroid surgery since he had the above high-risk factors of postoperative HBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease has been studied for more than 40 years. Recently, this has become one of the most dynamic topics in hormonally active adrenal lesions due to significant progress in steroid metabolomics, molecular genetics of the immune CYP11B1/B2 gene constellation, and newly developed pathological types in the 2022 WHO classification ( 6 ). Lihua Hu et al described the management of a 49-year-old woman with coexisting primary aldosteronism (PA) and subclinical Cushing's syndrome due to a right adrenal adenoma.…”
Section: Primary Aldosteronism and Subclinical Cushing Syndromementioning
confidence: 99%
“…Co-secretion of aldosterone and cortisol from an adrenal tumour can lead to the development of Connshing (CoSh) syndrome. 60 ACTH dependent and independent CS can rarely co-exist. 61 Though the common components of Multiple Endocrine Neoplasia 2 (MEN2) are primary hyperparathyroidism, PCC, and medullary thyroid cancer, it can rarely cause ACTH dependent CS (both Cushing' disease and ectopic ACTH or CRH secretion).…”
Section: Other Endocrine Causes Of Hypertensionmentioning
confidence: 99%